A critical analysis of the existing: Maqasid-based welfare indices - Suliswanto, Muhammad Sri Wahyudi; Mohd Yusop, Mohd Mahyudi; Barom, Mohd Nizam (Maqasid Institute, 2024)
Abstract Maqasid al-Shariah based welfare measurement is a welfare measurement tool that covers all dimensions of welfare, both material and non-material. According to the Maqasid al-Shariah theory put forward by Al-Ghazali and Al-Shatibi; which was later expanded further into the socio-economic context. Chapra then suggested the need to expand the application of al-Maqasid to make it more practical and effective because al-Maqasid is a philosophical principle that needs to be simplified so that it can be put into practice. Many contemporary researchers apply Maqasid al-Shariah in measuring development or welfare instruments with various modifications related to the sub-variables. However, most give equal weight to each component of maqasid even though most Muslim scholars give different priorities to each component of maqasid. Therefore, this study will criticize fifteen articles on the maqasid-based welfare index as a first step in proposing improvements to the measurement of the maqasid-based welfare index. To achieve the research objectives, the method used in this research is an integrative literature review. This study proposes an index and indicator model to integrate the five dimensions of Maqasid al-Shariah in measuring welfare.